An activity monitoring system for senior citizens living independently using capacitive sensing technique - Arshad, Atika; Khan, Sheroz; Alam, A.H.M Zahirul; Tasnim, Rumana; Gunawan, Teddy Surya; Ahmad, Robiah; Nataraj, Chandrasekharan (Institute of Electrical and Electronics Engineers Inc., 2016)
With the continual increase of senior citizens more resources are required for providing care centers services. The quality of such services can be enhanced by remotely monitoring senior citizens living independently in their homes. The monitoring can be performed using various types of sensors, but the solution presented in this paper is simple, cost effective as well as easy to implement compared to most of the existing systems. The proposed system uses capacitive based sensor to monitor the daily activities of an elderly living alone. The monitoring system works on the principle of measuring the disturbance in the electromagnetic field when a human body approaches the sensor. This proposed sensor is fundamentally based on electric field sensing using sensors are in the form of thin planar electrodes. The Arduino-based board in combination with CapSense library acquires the sensed data. The detection system is embedded on the care-center floor surface, making the system to be non-intrusive as well as maintaining the privacy of the user. The data so obtained is perceived as information on a PC, which can be used in generating an automatic alarm system. A notification can be sent to the cell phones of the caregivers for assistance. The important thing in the alarms is that no user input is required from the person under monitoring and no devices need to be worn. A prototype sensor is described in detail and preliminary results are presented based on simulation and experimental procedure.